Penyusunan Model Kerja Sama Ciayumajakuning - Budiyono, Haris (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2011)
Alternative models of inter regency/city cooperation should be designed by West Java Province Governance to encourage those regencies/cities in West Java Province in actuating a form of partnership among them, particularly to respond the spirit of those regencies/city in Ciayumajakuning region (Kabupaten Cirebon, Kota Cirebon, Kabupaten Indramayu, Kabupaten Majalengka, dan Kabupaten Kuningan), since they intended to foster cooperation among their local governments. The study of designing alternative models was done by PUSKOTDA on September-November 2010, it was carried out in 4 four steps : (1) Study on those regulations relevant to inter regency/city cooperation, (2) Academic Review, (3) Formulated those models, and (4) FGD to discuss opinions and ideas toward a concept of inter regency/city cooperation. Focus groups recommended that a suitable concept for inter regency/city cooperation of Ciayumajakuning is a regional management, to explore, develop, and empower economic capacities of Ciayumajakuning. Four main aspects are also recommended to be done by this body : firstly institutionalized of the efforts, secondly human resources capacity development to pursue a competitive advantages of the region, and thirdly developing a good climate for investment, and lastly to encourage an engagement of local business owners in the region and public participation to accelerate the economic empowering partnership in the region.